Geologiske undersøkelser i sørlige Helgeland og nordlige Namdal. - Kollung, Sigbjørn (1967)
Cambro-Silurian rocks with large intrusive masses cover most of the area. In the south-westernmost part there are also deeper lying rocks. This part is referred to as the basal gneiss region, while the rest of the area is called the Nordland syncline. In the basal gneiss region there are 3 distinct stratigraphic units: 1. Basal gneisses of supposed Pre-cambrian age. 2. Lower Cambro-Silurian division: micaceous gneisses. 3. Upper Cambro-Silurian division: lime-silicate gneisses with amphibolites and micaceous gneisses, the greater part of which is dark, rather basic and transitional to hornblende-bearing gneiss. Locally also crystalline lilmestone. The three rock units in the basal gneiss region are intensly folded together, and the boundaires between them are concordant. It is thus clear that the basal gneiss has been strongly influenced by the Caledonien orogeny. Steeplimbed, isoclinal folds are most common, but some well-developed synclines and anticlines are present. The greater part of the region has a strike direction ENE to NE. In the northernmost part the fold axes have a northerly plunge. At Tenfjord lime-slicate gneisses are thrust towards the basal gneiss.The northern and greater part of the Nordland has an approximate synform. 34941